Electrometric studies on formation of cerium vanadates as a function of pH - Prasad,S. (2006)
The precise nature of the reaction between nitric acid and sodium ortho-vanadate solutions has been studied by means of electrometric techniques involving potentiometric and conductometric titrations. The well defined inflections and breaks in the titration curves confirm the existence of the anions, pyro-V2O7(4-), meta-VO3- and poly-H2V10O28(4-) corresponding to the ratios of VO4(3-):H+ as 1:1, 1:2 and 1:2.6 in the neighborhood of pH 10.5, 7.4 and 3.6, respectively. The interaction of cerium(III) nitrate with sodium vanadate solutions, at specific pH levels 12.4, 10.5, 7.4 and 3.6 was also studied by potentiometric and conductometric titrations between the reactants. The end-points obtained from the sharp inflections in the titration curves provide definite evidence for the formation and precipitation of cerium ortho-Ce2O3.V2O5, pyro-2Ce2O3.3V2O5 and meta-Ce2O3.3V2O5 vanadates in the neighborhood of pH 7.4, 6.2 and 4.8, respectively. Analytical investigations on the precipitates formed confirm the results of the electrometric study.